The quality of clinical practice guidelines for preoperative care using the AGREE II instrument: A systematic review - Ciapponi, Agustín (2020)
Background: Our aim was to summarize and compare relevant recommendations from evidence-based CPGs (EB-CPGs). Methods: Systematic review of clinical practice guidelines. Data sources: PubMed, EMBase, Cochrane Library, LILACS, Tripdatabase, and additional sources. In July 2017, we searched CPGs that were published in the last 10 years, without language restrictions, in electronic databases, and also searched specific CPG sources, reference lists, and consulted experts. Pairs of independent reviewers selected EB-CPGs and rated their methodological quality using the AGREE-II instrument. We summarized recommendations, its supporting evidence, and strength of recommendations according to the GRADE methodology. Results: We included 16 EB-CPGs out of 2262 references identified. Only nine of them had searches within the last 5 years and seven used GRADE. The median (percentile 25-75) AGREE-II scores for rigor of development was 49% (35-76%) and the domain "applicability"obtained the worst score 16% (9-31%). We summarized 31 risk stratification recommendations, 21.6% of which were supported by high/moderate quality of evidence (41% of them were strong recommendations), and 16 therapeutic/preventive recommendations, 59% of which were supported by high/moderate quality of evidence (75.7% strong). We found inconsistency in ratings of evidence level. "Guidelines' applicability"and "monitoring"were the most deficient domains. Only half of the EB-CPGs were updated in the past 5 years. Conclusions: We present many strong recommendations that are ready to be considered for implementation as well as others to be interrupted, and we reveal opportunities to improve guidelines' quality.